(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2022)
Sipakatau is manifestation of the local cultural values of the Bugis tribe. Locality culture which includes the understanding of norms and customary rules and regulations which cover all activities of human life, behavior, and regulate the infrastructure of life in the form of material and non-material equipment. This study aims at describing the phenomenological study of the development of Bugis self-awareness and to describe the phenomenological study of the development of self-control in the Bugis community. The research object is Bugis culture in the book Sipakatau by Muhammad Huzain et al.The research method used was a qualitative descriptive method. The data from this study were sentences and paragraphs related to phenomenology. The data collection technique was a purposive sampling technique, namely the researcher only took data related to literary phenomenology. The research results show about Self-control Form of the Bugis community in the Sipakatau book, Pride. One of the things that is the most important part of the culture of attitude, namely self-esteem, the principle of life without the principle of human life is considered to have no direction and purpose. Honesty (getteng) is also part of the Bugis self-control. Honesty is a basis in good deeds whose existence cannot be changed.